Successful Rate of Glaucoma Surgery in Secondary Glaucoma after Vitrectomy in Kariadi General Hospital Semarang 2020-2022: Oral Presentation - Observational Study - Resident - Maharani; Ismail, Nur Azizah Intan Putri; Rahmi, Fifin L.; Puspasari, Denti (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesGlaucoma is one of the most frequent complications of vitrectomy surgery. It can cause a significantrise in intraocular pressure (IOP). Glaucoma surgery can be planned in medically uncontrolledglaucoma. Trabeculectomy and Glaucoma Drainage Device (GDD) implantation are the mostfrequent filtering surgeries used in these cases. This study aims to define the success rate ofglaucoma surgery in secondary glaucoma after vitrectomy. MethodsThis study is an analytical observational study with retrospective data collection held from medicalrecords of patients with secondary glaucoma after vitrectomy who underwent glaucoma surgery inKariadi General Hospital Semarang from 2020-2022. Surgical success defined by postoperative IOPreduced by>20% from baseline, with or without anti-glaucoma medication. ResultsThere were 16 eyes of trabeculectomy with 5-fluorouracil (5-FU), and 8 eyes of GDD implants. Themean preoperative IOP was 43.76+6.77 mmhg for trabeculectomy 5-FU, and 42.43+4.02 mmhg forGDD implant. IOP levels in both groups varied significantly after one day, one week, one month, andthree months after surgery (p<0.05). The success rate for the trabeculectomy 5-FU group was81.25% and the GDD implant group was 87.5% in 3 months. There was no statistically significantdifference in the success rate between the trabeculectomy 5-FU and GDD implant groups (p=0.839).The complication for the GDD implant group was 25%. No complications were found in thetrabeculectomy 5-FU group. ConclusionThere was no significant difference in the success rate between trabeculectomy 5-FU and the GDDimplant group. Both groups are viable for glaucoma surgery in secondary glaucoma after vitrectomysurgery.